Receptor-like leucine-rich repeat kinases of subfamily III are involved in the recognition of Pectobacterium spp. by Solanaceae plants - E. V. Shrub; N. V. Kalubaka; P. V. Vychyk; O. A. Badalyan; Y. A. Nikolaichik (Вавиловский журнал генетики и селекции, 2025)
The genomes of Solanaceae plants contain over 600 receptor-like protein kinase genes with leucine-rich repeats (LRR-RLK), many likely associated with pathogen detection, but very few functionally characterized. Pectobacterium spp. are the major bacterial pathogens of agricultural crops, particularly potatoes and other Solanaceae plants. For relevant potato pathogens from the genus Pectobacterium, specific immune receptors have not been described in Solanaceae. However, in Malus × domestica, four LRR-RLK from the LRRIII subfamily (DIPM1-4) have been characterized as receptors for the related pathogen Erwinia amylovora. DIPMs specifically interact with the effector protein DspE and are involved in E. amylovora recognition. Since the DspE ortholog is also the main effector in Pectobacterium spp., we performed a phylogenetic analysis of LRRIII subfamily receptors in the most relevant Solanaceae representatives together with a much better characterized LRR-RLKIII of Arabidopsis thaliana and identified nine clusters of related RLKs. Clustering followed by analysis of published data allowed us to functionally characterize this RLK family and suggest the most likely candidates for checking interactions with the main effector of pectobacteria, DspE. Testing the kinase domains of representative cluster members in a yeast two-hybrid system revealed four Solanaceae RLKs interacting with the DspE effector from Pectobacterium versatile. Virus-induced silencing of these RLK genes demonstrated their involvement in P. versatile recognition. The RLK6 gene from Solanum bulbocastanum, which is not an ortholog of the DIPM proteins in apple, seems to be the most promising potential resistance gene. This work expands our understanding of LRR-RLKIII subfamily RLKs and their role in plant immunity, providing a foundation for future development of disease-resistant Solanaceae varieties.